Additive friction stir processing - Lin, Longyi (2014)
Additive manufacturing (AM) presents huge potential in the present drive for sustainable manufacturing. This work examined the feasibility of using multi-pass Friction Stir Processing (FSP) as an AM technique, with comparisons to the widely used Selective Laser Melting (SLM) method. Multi-pass FSP was successfully performed in joining two AA6061-T6 plates, with and without Carbon Nanotubes (CNTs) reinforcement, using FSP parameters of 1800RPM rotation rate, 8mm/s traverse speed, 3.6-4.2kN downward force and 3o tilt angle. The intense material mixing during FSP resulted in simultaneous dissolution and coarsening of strengthening particles, leading to lower microhardness and tensile strengths as the effect of Orowan strengthening was reduced. However, the particles became smaller and more homogeneously distributed as the number of FSP passes increases. The continuous dynamic recrystalisation during FSP also gave finer grains, which was further enhanced with the addition of CNTs through Zener pinning effect. The improvement in tensile strengths due to finer grains through the Hall-Petch mechanism was insufficient to compensate for the drop in Orowan strengthening. Ductility improved due to enhanced dynamic recovery and grain boundary sliding/rotation. As AA6061 was found to have low success rate under SLM, comparative analysis was done on SLM AlSi10Mg specimens instead, to better understand the mechanical properties of SLM parts. The SLM AlSi10Mg, with a density of nearly 99.5%, was found to have comparable mechanical properties to heat treated cast AlSi10Mg. The grain size of the SLM specimens was close to that of monolithic FSP specimens, indicating that their higher strengths and microhardness is likely a result of the dense Si phase formed. However, similar to casting, the SLM specimens were brittle and had visible internal defects that acted as nucleation sites for cracks. Hence, future studies could look into improving the properties of SLM parts through FSP.